Vibrational Analysis and Quantum Chemical Calculations of 2,2′-Bipyridine Zinc(II) Halide Complexes - Özel, Ayşen E.; Kecel Gündüz, Serda; AKYÜZ, SEVİM (Elsevier, 2007)
In this study the molecular structure and vibrational spectra of Zn(2,2′-bipyridine)X2 (X = Cl and Br) complexes were studied in their ground states by computational vibrational study and scaled quantum mechanical (SQM) analysis. The geometry optimization, vibrational wavenumber and intensity calculations of free and coordinated 2,2′-bipyridine were carried out with the Gaussian03 program package by using Hartree–Fock (HF) and Density Functional Theory (DFT) with B3LYP functional and 6-31G (d,p) basis set. The total energy distributions (TED) of the vibrational modes were calculated by using Scaled Quantum Mechanical (SQM) analysis. Fundamentals were characterised by their total energy distributions. Coordination sensitive modes of 2,2′-bipyridine were determined.
Keywords: Ab Initio Calculations; Hartree–Fock; DFT; Bipyridine; Halide Complexes; Vibrational Frequencies